Dual‐Template Pore Engineering of Whey Powder‐Derived Carbon as an Efficient Oxygen Reduction Reaction Electrocatalyst for Primary Zinc‐Air Battery. Issue 12 (14th May 2020) - Yan, Shunyao; Yu, Zixun; Liu, Chang; Yuan, Ziwen; Wang, Chaojun; Chen, Junsheng; Wei, Li; Chen, Yuan
Abstract: Cost‐effective and high‐performance electrocatalysts for oxygen reduction reactions (ORR) are needed for many energy storage and conversion devices. Here, we demonstrate that whey powder, a major by‐product in the dairy industry, can be used as a sustainable precursor to produce heteroatom doped carbon electrocatalysts for ORR. Rich N and S compounds in whey powders can generate abundant catalytic active sites. However, these sites are not easily accessible by reactants of ORR. A dual‐template method was used to create a hierarchically and interconnected porous structure with micropores created by ZnCl2 and large mesopores generated by fumed SiO2 particles. At the optimum mass ratio of whey power: ZnCl2  : SiO2 at 1 : 3 : 0.8, the resulting carbon material has a large specific surface area close to 2000 m 2  g −1, containing 4.6 at.% of N with 39.7% as pyridinic N. This carbon material shows superior electrocatalytic activity for ORR, with an electron transfer number of 3.88 and a large kinetic limiting current density of 45.40 mA cm −2 . They were employed as ORR catalysts to assemble primary zinc‐air batteries, which deliver a power density of 84.1 mW cm −2 and a specific capacity of 779.5 mAh g −1, outperforming batteries constructed using a commercial Pt/C catalyst. Our findings open new opportunities to use an abundant biomaterial, whey powder, to create high‐value‐added carbon electrocatalysts for emerging energy applications. Abstract : Pore structures of whey powder‐derived carbon materials are engineered by using ZnCl2 and SiO2 particles as dual templates. A large surface area of 1944 m 2  g −1 is obtained at an optimal mass ratio of whey powder : ZnCl2  : SiO2 =1 : 3 : 0.8, which delivers excellent catalytic activity for the oxygen reduction reaction.